Prenatal Exposure to PM2.5 and Infant Birth Outcomes: Evidence from a Population-Wide Database - Babak Jahanshahi; Brian Johnston; Duncan McVicar; Mark McGovern; Dermot O'Reilly; Neil Rowland; Stavros Vlachos (Queen's University Belfast, Queen's Management School, 2022)
There are growing concerns about the impact of pollution on maternal and infant health. In the UK in 2018, 36% of local authorities had levels of PM2.5 where exposure exceeded the annual level recommended by the World Health Organisation at the time. Using a population database of births in Northern Ireland linked to localised geographic information on pollution in mothers' postcodes (zip codes) of residence during pregnancy, we examine whether prenatal exposure to PM2.5 is associated with a comprehensive range of birth outcomes. Overall, we find little evidence that particulate matter is related to worse infant outcomes once we implement a fixed effects approach that accounts for time-invariant factors common to mothers. While reducing pollution remains an urgent public health priority, our results imply that improvements in short-run levels of prenatal PM2.5 exposure are unlikely to be sufficient by themselves to reduce disparities in birth outcomes.
Keywords: I10; J10; Q53; 330; Pollution; PM2.5; infant outcomes; sibling fixed-effects; birth weight